Analisis Kepuasaan Masyarakat terhadap Penggunaan Aplikasi JKN Mobile dengan Menggunakan Metode Servqual Di Klinik Beringin - Nur Lutfiyana; Ivan Cahya Firmana; Salsa Gusti Amalia; Teuku Aldi Syahputra (Jurnal Sistem Informasi, 2023)
Abstract— The Social Security Administering Body (BPJS) as the provider of national health insurance for all Indonesians seeks to improve the service system for all BPJS Health participants. BPJS Health innovates by launching the JKN Mobile application, with the JKN Mobile application it is expected to be able to provide convenience for users to get more optimal services. With the JKN Mobile application, it is also hoped that users can access various kinds of information related to JKN programs easily and quickly and can access anytime and anywhere. This study aims to determine the relationship between services on the JKN Mobile application and the level of satisfaction of BPJS Health users at Beringin Clinicl.